2022
DOI: 10.3389/fmolb.2022.828766
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Bronchial Epithelial Cell Epithelial Mesenchymal Transition Through Regulating Endoplasm Reticulum Stress

Abstract: Epithelial mesenchymal transition (EMT) is a contributing factor in remodeling events of chronic obstructive pulmonary disease (COPD). Hydrogen sulfide (H2S) has been implicated in the pathogenesis of COPD, but the effect of H2S in regulating EMT and the underlying mechanisms is not clear. In this study, we assessed endoplasmic reticulum (ER) stress markers, EMT markers and associated signal molecules in rat lungs, bronchial epithelial cells, and human peripheral lung tissues to investigate the effect of H2S i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…H 2 S upregulated sirtuin 1 expression, which improved mitochondrial function and reduced oxidative stress; thus, cell senescence induced by cigarette smoke was attenuated ( Guan et al, 2019 ). Hydrogen sulfide also inhibits EMT by regulating endoplasm reticulum stress (ERS) ( Lin et al, 2022 ). With ERS markers such as glucose-regulated protein-78 (GRP78), C/EBP homologous protein (CHOP), and caspase-12 were reduced in the COPD rat model that was established by passive smoke exposure and lipopolysaccharide irritation, pulmonary artery endothelial cell apoptosis was decreased ( Ding et al, 2018 ).…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…H 2 S upregulated sirtuin 1 expression, which improved mitochondrial function and reduced oxidative stress; thus, cell senescence induced by cigarette smoke was attenuated ( Guan et al, 2019 ). Hydrogen sulfide also inhibits EMT by regulating endoplasm reticulum stress (ERS) ( Lin et al, 2022 ). With ERS markers such as glucose-regulated protein-78 (GRP78), C/EBP homologous protein (CHOP), and caspase-12 were reduced in the COPD rat model that was established by passive smoke exposure and lipopolysaccharide irritation, pulmonary artery endothelial cell apoptosis was decreased ( Ding et al, 2018 ).…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…In addition to modulating the NLRP3 inflammasome, IRE1α can promote CS-induced airway inflammation by activating the NF-κB signaling pathway [ 129 , 130 ]. Furthermore, the activation of IRE1α played a crucial role in the nicotine-induced epithelial-mesenchymal transition and decreased cell migration capacity in human bronchial epithelial cells [ 152 ]. Epithelial-mesenchymal transition is a pivotal contributor to airway remodeling in COPD.…”
Section: Copd and Er Stressmentioning
confidence: 99%
“…Scavenging the haem with salubrinal (eIF2α dephosphorylation inhibitor) suppressed ER stress, reduced elastase levels and activity, and attenuated the development of fibrosis and emphysema pathophysiological phenotypes in COPD. Hydrogen sulfide (H2S), as an endogenous modulator, attenuated smoke-induced apoptosis and epithelial-mesenchymal transition by inhibiting ER stress, thus hindering the progression of lung function decline and emphysema formation in rats [ 152 , 158 , 159 ]. Melatonin counteracts CS-induced inflammasome activation and apoptosis by inhibiting ER stress and mitochondrial dysfunction [ 129 , 160 ].…”
Section: The Upr and Potential Therapeutic Interventions In Copdmentioning
confidence: 99%
“…Additionally, H 2 S, as an endogenous modulator, alleviated CS-induced rat lung cell apoptosis and Epithelial-Mesenchymal Transition (EMT) by suppressing endoplasmic enzyme stress, thereby impeding the progression of lung function decline and emphysema formation. [28][29][30] It has also been reported that melatonin inhibits ERS and mitochondrial dysfunction, counteracting CS-induced inflammasome activation and apoptosis. 31,32 The specific relationships between key genes and clinical indicators were also analyzed in the study.…”
mentioning
confidence: 99%